E-retailers and the engagement of delivery workers in urban last-mile delivery for sustainable logistics value creation: Leveraging legitimate concerns under time-based marketing promise. (May 2020) - de Kervenoael, Ronan; Schwob, Alexandre; Chandra, Careen
Abstract: This paper's research aims to understand how e-retailers can benefit from independent contractors' (delivery drivers') agile engagement under time-based marketing promise (TBMP) to advance sustainable logistics value creation in the urbanised last-mile-delivery (ULMD) environment. Our analysis of independent drivers' narratives (n = 30) reveals that sustainable logistics value can be apprehended through a process in which independent workers are both agenced by their leveraging of technologisation and task autonomy and concerned by the mobilisation of other ULMD stakeholders. They thus can propose novel, creative solutions for e-retailers and city planners towards sustainable logistics value creation.